If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5x + 8) = 3x + -23 Reorder the terms: -2(8 + 5x) = 3x + -23 (8 * -2 + 5x * -2) = 3x + -23 (-16 + -10x) = 3x + -23 Reorder the terms: -16 + -10x = -23 + 3x Solving -16 + -10x = -23 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -16 + -10x + -3x = -23 + 3x + -3x Combine like terms: -10x + -3x = -13x -16 + -13x = -23 + 3x + -3x Combine like terms: 3x + -3x = 0 -16 + -13x = -23 + 0 -16 + -13x = -23 Add '16' to each side of the equation. -16 + 16 + -13x = -23 + 16 Combine like terms: -16 + 16 = 0 0 + -13x = -23 + 16 -13x = -23 + 16 Combine like terms: -23 + 16 = -7 -13x = -7 Divide each side by '-13'. x = 0.5384615385 Simplifying x = 0.5384615385
| -3(-4Z+-5)= | | x=45+12x | | (2a+3)(3a-4)= | | 9=4+5x | | 75-x=x+5 | | 0.25+2x=360 | | 5y+9-y=26 | | 0.9(7x+4)=0.7-(x-3) | | 10t-6-t=9t-6 | | -10+10+-5B*2+-1+-5B= | | 4x-2+x=-2+2 | | 3(3x-8)=4x-6 | | 51x+18-29x=131 | | 8a-(1+5a)=4(3a-11)-24 | | 11b+4=37 | | 11x+8+17x-17=13x+79 | | m=m(c)2 | | 3m-1-6=13+7m | | w+2=-43-8t | | 28b^2-80b-12= | | 4x+35-15=9x-45 | | 3n+8=57 | | 1.8x+1.2x-5.4=-10 | | 2w(4w-1)=w(1-4w) | | 3(2x-1)=9x+3 | | 1a=-5a | | 0.08(x-100)=83.5-0.07 | | 3n+4=57 | | 5y+10-y=29 | | f(x)=x^2-4x-44 | | -8(v+7)+8=-33-5v | | Y+5-9=10 |